Successful cryopreservation of matured testis and ovary for the short barbeled velvetchin (Hapalogenys nitens) - Zhou, Li; Li, Feiyan; Han, Kunhuang; Sun, Zhaohan; Chen, Jia; Zheng, Shizhong (Frontiers in Marine Science, 2025)
As an important germplasm resource of fish, the cryopreservation of testis and ovary is of great significance to protect endangered species and increase genetic diversity. However, current methods of slow cooling and vitrification in gonad preservation require a specialized cooling equipment or a higher concentration of cryoprotectants to maintain cell viability. The short barbeled velvetchin (Hapalogenys nitens) is an important marine economic fish, and the germplasm resources have been degraded during long-term artificial breeding. Therefore, this study isolated the gonads of mature Hapalogenys nitens and investigated the cryopreservation effect of testis and ovary with three cryoprotectant combinations under four freezing procedures. The results showed that the gonad tissues were cut to blocks of 0.5 cm3, which could effectively cryopreserve the testes or ovaries with the cryoprotectant combinations of 15% ethylene glycol, 10% dimethyl sulfoxide, 0.2 M trehalose or 15% propylene glycol, 0.2 M trehalose, and 15% fetal bovine serum, respectively. The testes with cryoprotectants were only kept 5 cm above liquid nitrogen for 10 min and then immersed in liquid nitrogen, while the ovaries soaked in cryoprotectants were directly stored in the refrigerator at -80°C. After 7 days, the gonads were thawed in a water bath at 10°C for 8 min and analyzed by morphology, and the cell viability was measured by trypan blue or cell viability assay kits, resulting in a high survival rate (>90%). The present study successfully established cryopreservation protocols of gonad tissues in Hapalogenys niten. This was a convenient, rapid, and efficient method for the gonad cryopreservation of Sparidae fishes and provided reference for the preservation of other fish germplasm resources.